Occurrence of c.976 G>T (p.Val326Leu) and c.452 G>A (p.Trp151Ter) variants in DHCR7 gene in population of polish women with recurrent miscarriage. (September 2020) - Chrzanowska - Steglińska, Marta; Moczulska, Hanna; Skoczylas, Beata; Pietrusiński, Michał; Antosik, Karolina; Jakiel, Paulina; Kacprzak, Marta; Borowiec, Maciej; Sieroszewski, Piotr
Abstract: Introduction: Recurrent miscarriage is a serious clinical problem that affects 1–5 % of all couples trying to conceive. Although the incidence of Smith-Lemli-Opitz Syndrome (SLOS, OMIM #270400), an autosomal recessive condition caused by variants in the DHCR7 gene, is very low, (1:83 000), the observed carrier frequency of DHCR7 gene variants in the Polish population is high, ranging from 1:24 to 1:31. It is possible that this carriage may be responsible for early pregnancy loss. Objectives: The aim of the study is to determine the carrier frequency of the p c.976 G>T (p.Val326Leu) and c.452 G>A (p.Trp151Ter) variants in the DHCR7 gene in patients experiencing recurrent miscarriage. Methods: The study group included 480 patients: a study group of 380 with at least 2 miscarriages before the 20th week of pregnancy, and a control group of 100 who had not experienced miscarriage. The variants were identified by genotyping: c.976 G>T (p.Val326Leu) by the TaqMan® SNP Genotyping Assay system, and c.452 G>A (p.Trp151Ter) using the BfaI restriction enzyme. Statistical analysis was performed using R software. Results: No examples of c.976 G>T (p.Val326Leu) were found in either group. c.452 G>A (p.Trp151Ter) was found in 22 participants from the study group and 4 from the control group; however, this difference was not significant (Chi2 test p = 0.61). Conclusions: Being a carrier of the c.976 G>T (p.Val326Leu) and c.452 G>A (p.Trp151Ter) variants in the DHCR7 gene is not a risk factor for recurrent miscarriage in the Polish population.